HIF2α‐induced upregulation of RNASET2 promotes triglyceride synthesis and enhances cell migration in clear cell renal cell carcinoma. Issue 4 (12th February 2023) - Quan, Yanmei; Dai, Jun; Zhou, Sian; Zhao, Lingyi; Jin, Lixing; Long, Yijing; Liu, Siwei; Hu, Yanqin; Liu, Yue; Zhao, Juping; Ding, Zhide
Abstract : Clear cell renal cell carcinoma (ccRCC), the most common malignant subtype of renal cell carcinoma, is characterized by the accumulation of lipid droplets in the cytoplasm. RNASET2 is a protein coding gene with a low expression level in ovarian cancers, but it is overexpressed in poorly differentiated neuroendocrine carcinomas. There is a correlation between RNASET2 upregulation and triglyceride expression levels in human serum but is unknown whether such an association is a factor contributing to lipid accumulation in ccRCC. Herein, we show that RNASET2 expression levels in ccRCC tissues and cell lines are significantly higher than those in both normal adjacent tissues and renal tubular epithelial cells. Furthermore, its upregulation is associated with increases in ccRCC malignancy and declines in patient survival. We also show that an association exists between increases in both cytoplasmic lipid accumulation and HIF‐2α transcription factor upregulation, and increases in both RNASET2 and triglyceride expression levels in ccRCC tissues. In addition, DGAT1 and DGAT2, two key enzymes involved in triglyceride synthesis, are highly expressed in ccRCC tissues. By contrast, RNASET2 knockdown inhibited their expression levels and lowered lipid droplet accumulation, as well as suppressing in vitro cell proliferation, cell invasion, and migration. In conclusion, our data suggest HIF2α upregulates RNASET2 transcription in ccRCC cells, which promotes both the synthesis of triglycerides and ccRCC migration. As such, RNASET2 may have the potential as a biomarker or target for the diagnosis and treatment of ccRCC. Abstract : In normal kidney, HIF2α exists at low levels in the cytoplasm under normal oxygen conditions. However, in VHL ‐deficient clear cell renal cell carcinoma (ccRCC), HIF2α accumulates in the cytoplasm under hypoxia and is then transported into the nucleus. HIF2α‐induced RNASET2 upregulation increases DGAT expression, thereby promoting triglyceride synthesis and cell migration in ccRCC.